Increase in the prevalence of the MTHFR 677 TT polymorphism in women born since 1959: potential implications for folate requirements - Agodi, A; Barchitta, M; Valenti, G; Marzagalli, R; Frontini, V; Marchese, A E (European journal of clinical nutrition, 2011)
Background/Objectives: Folate has been recognized to ensure reproductive health and there is a growing body of epidemiological evidence suggesting that the methylenetetrahydrofolate reductase ( MTHFR ) 677T allele and reduced dietary folate may increase the risk of cervical cancer. The main focus of our survey was to investigate the distribution of the MTHFR C677T polymorphism in relation to women's year of birth and to assess their folate intake and folic acid supplementation. Subjects/Methods: During a 6-months period, 307 healthy women of childbearing age in Catania, Italy, were enrolled in the cross-sectional study. Folate intake was estimated by a semiquantitative food frequency questionnaire and DNA extracted from blood samples for MTHFR C677T genotyping. Results: A TT genotype frequency of 20.5% with an increase in the prevalence of the TT genotype in the cohort of women born since 1959 was shown. The prevalence of inadequate folate intake was 51.5%, significantly higher in non-pregnant women (83.4%) than in pregnant ones (12.3%) with a decrease during the three trimesters of pregnancy (from 25.7 to 5.0%; P =0.013). The use of folic acid supplements improved during the three trimester of pregnancy (from 71.4 to 95.0%; P =0.001). Conclusions: Healthy young women may have higher folate needs due to increasing prevalence of the T allele and reduced folate intake compared with older groups. However, clinicians should be cautious when recommending supplements to women in late pregnancy due to the possible implications in the pregnancy outcome.